Caregiver Feeding Behaviours and Child Dietary Diversity and Growth in Rural Bangladesh - Zaynah T. Chowdhury; Kristen M. Hurley; Saijuddin Shaikh; Sucheta Mehra; Hasmot Ali; Abu Ahmed Shamim; Parul Christian (Maternal and Child Nutrition)
ABSTRACT This study examined relations between caregiver feeding behaviours, child dietary diversity and anthropometry at 24 months of age in rural Bangladesh. Twenty‐four hours dietary recall, weight and length data were collected on 4733 children. Factor analysis was applied to an 11‐item caregiver feeding behaviours scale administered at 24 months, revealing two constructs: responsive/involved (five items) and forceful (six items); each dichotomised to reflect low and high use. Stunting (length‐for‐age Z‐score < −2), wasting (weight‐for‐length Z‐score < −2) and underweight (weight‐for‐age Z‐score < −2) were defined using international growth reference standards. Associations between feeding behaviours, dietary diversity score (DDS, food groups consumed; range 0–7) and anthropometric indicators were examined using multivariable linear or logistic regression models, adjusting for study design, confounders and intervention arm. Mean (SD) age of children in the study was 24.1 (0.3) months. Mean (SD) DDS was 3.7 (1.4), with 55% of children meeting minimum dietary diversity (MDD, DDS ≥ 4). Stunting, wasting and underweight were 40%, 19% and 42%, respectively. Use of high responsive/involved feeding behaviours (reported in 71% of mothers) was associated with higher DDS (0.09, 95% confidence interval [CI]: 0.001, 0.17) and higher odds of achieving MDD (OR: 1.17; 95% CI: 1.02, 1.33) but not with anthropometric outcomes. Use of high forceful feeding behaviours (reported in 34% of mothers) was associated with lower DDS (−0.12, 95% CI: −0.21 to 0.04), lower odds of achieving MDD (OR: 0.82, 95% CI: 0.72, 0.93), and higher odds of underweight (OR: 1.38, 95% CI: 1.22, 1.56) and wasting (OR: 1.55, 95% CI: 1.33, 1.81). In Bangladesh, responsive/involved feeding was associated with higher child dietary diversity whereas forceful feeding was associated with lower dietary diversity and undernutrition. Future research is needed to understand causality and test the effect of responsive feeding interventions on the promotion of child growth.